STRATEGI MENINGKATKAN MOTIVASI BELAJAR SISWA SEKOLAH DASAR SEBAGAI UPAYA MENGATASI PUTUS SEKOLAH - Grasiara Naya S; Mery Suryanti; Hana Faridah (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2024)
The generation of elementary school students dropping out of school is still a massive phenomenon in Matang Segarau village. So that it becomes a highlight and priority for villages that make extra efforts to overcome this problem. According to village data, 28 people who did not attend school were still found. Apart from that, in terms of education, there were 120 graduates from elementary school (SD), followed by second-place graduates from junior high school (SMP) with 105 people. This data shows that graduates at the 9 (nine) year Compulsory Education level are still low. This means that the higher the education, the fewer people have it. Solving this problem is a joint task for all stakeholders in the Matang Segarau village, attracting the author to conduct research in this village, intended to solve the problems that occur. The research method used is a qualitative empirical study method (field research) by identifying problems that occur directly at the location. Using a qualitative approach and data collection techniques through observation and interviews. The purpose of this research is to determine the factors that cause students to drop out of school, then the factors that cause a lack of motivation to learn, and obstacles in the learning process of elementary school students by formulating strategies to increase learning motivation in elementary school students so that they want to continue their studies to higher education. So, the results of this research are hoped to solve problems and be a solution in efforts to overcome elementary school dropouts in Matang Segarau village, Tekarang District, Sambas Regency, West Kalimantan Province.